Ornament in the Architecture of the 20th Century: Classics and Discourse - Sharapov Ivan A. (Художественная культура)
The study is devoted to the specifics of ornament in the context of architecture and at the same time it clarifies one of the challenges of the 20th century architecture — the rejection of ornament, which was manifested by the American architect L. Sullivan and the Austrian modernist A. Loos, who became key participants in the trend for the rejection of ornament in modern architecture. The article investigates the theoretical premises of the rejection and clarifies the formative specifics of ornament considering conceptual approaches in the theory and practice of architecture. As a result of the study, it was found that the classical subjectivity of ornament was naturally transformed into a conceptual spatial structure, as evidenced by the verbal statements and texts of the architects. Based on this, the phenomenon of ornament appears in a different light — the conceptual one. Based on the analysis of the facts of texts, a conclusion is drawn about the renewal of the function of ornament in the architecture of the 20th century.